2002
DOI: 10.1093/toxsci/69.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Troglitazone on HepG2 Viability and Mitochondrial Function

Abstract: Troglitazone (TRO), a member of the thiazolidinedione class of drugs, has been associated with hepatotoxicity in patients. The following in vitro study was conducted to investigate the effects of TRO on mitochondrial function and viability in a human hepatoma cell line, HepG2. TRO induced a concentration- and time-dependent increase in cell death, as measured by lactate dehydrogenase release. Exposure to 50 or 100 micro M TRO produced total loss of cell viability within 5 h. Preincubation of HepG2 cells with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 30 publications
(36 reference statements)
6
44
0
Order By: Relevance
“…Mitochondrial abnormalities have been described in cultured cells and human cells exposed to TZD. Thus, Tirmenstein et al 40 and Shishido et al, 39 in cultured hepatocyte lines treated with troglitazone, found enlarged mitochondria with reduced matrical density, abnormal cristae, and occasionally electron-dense deposits resembling myelin-like bodies. Likewise, Caldwell et al 8 identified an increased number of enlarged mitochondria containing crystals in liver cells of patients treated with 400 mg/day troglitazone for 6 months.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mitochondrial abnormalities have been described in cultured cells and human cells exposed to TZD. Thus, Tirmenstein et al 40 and Shishido et al, 39 in cultured hepatocyte lines treated with troglitazone, found enlarged mitochondria with reduced matrical density, abnormal cristae, and occasionally electron-dense deposits resembling myelin-like bodies. Likewise, Caldwell et al 8 identified an increased number of enlarged mitochondria containing crystals in liver cells of patients treated with 400 mg/day troglitazone for 6 months.…”
Section: Discussionmentioning
confidence: 95%
“…38 A number of authors have reported that troglitazone produces mitochondrial changes in a hepatocyte cell line 39 and in HepG2 cells. 40 Scatena et al 41 and Brunmair et al 42 have demonstrated that PPAR-ligands decrease respiratory control, induce uncoupling of the oxidative phosphorylation, and reduce the activity of complex I in cell culture and tissue homogenates. These effects of PPAR-ligands are likely due to a direct interaction of these agents with the enzyme complex, because they inhibited complex I in sonicated tissue homogenates containing disrupted mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…However, TGZ metabolite-protein adducts have only been demonstrated in liver microsomal preparations from rats with various cytochrome P450 (P450) inducers or in "supersomes" (cDNA-expressed human P450) (He et al, 2004). Furthermore, although TGZ is cytotoxic to human HepG2 cells and to rat and human hepatocytes in vitro, inhibitors of enzymes responsible for TGZ metabolism do not protect against TGZ-induced cytotoxicity (Kostrubsky et al, 2000;Yamamoto et al, 2001;Tirmenstein et al, 2002). HepG2 cells transfected with CYP3A4 or incubated with microsomes containing cDNA-expressed CYP3A4 metabolized TGZ, leading to increased cytotoxicity (Vignati et al, 2005).…”
Section: B Example: Troglitazonementioning
confidence: 99%
“…An example of TZD which had high impact in the clinic is troglitazone (TRO), introduced in 1997 but soon withdrawn from the market because of reports of serious hepatotoxicity, receiving a black box warning from the U.S. Food and Drug Administration (FDA). In fact, TRO, when incubated with HepG2 cells, decreased cellular ATP and  (Tirmenstein, Hu et al, 2002;Bova, Tam et al, 2005). Lim et al also demonstrated that TRO increases intramitochondrial oxidative stress that activates the Trx2/Ask1 pathway, leading to mitochondrial permeabilization (Lim, Liu et al, 2008).…”
Section: Anti-diabetic Agentsmentioning
confidence: 98%